Stakeholders and partnership mapping, and capacity and gender gap assessment for scaling of small ruminant value chain innovations - Getachew, Tesfaye; Rischkowsky, Barbara A.; Rekik, Mourad; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Small ruminant value chain development started in Ethiopia as part of Livestock and Fish CRP in 2012 in seven sites representing different regions of Ethiopia, production systems and communities. The objective of the initiative was to test technological and institutional innovations that would transform the small ruminant value chain and this involved rigorous procedures. Over the years, we have pilot tested many innovations along the small ruminant value chain which were found to be technically sound to be implemented, financially feasible and resulted in improvement of the livelihood of communities. Most of the proven technologies were also evaluated from environmental sustainability lens too focusing on sustainably increasing small ruminant productivity and incomes, adapting, and building resilience to climate change and reducing greenhouse gas emissions, where possible. Therefore, we believe the technologies are ready to scale. Upscaling the small ruminant value chain innovations require engaging many institutions and partners. Partnership between ICARDA/AICCRA and other research and development partners is crucial to sustain the program. This includes stakeholder mapping, analyzing their role, identify capacity and gender gap. Establishment of strategic partnerships among partners is an essential element in enhancing the efficiency of the upscaling operation.